A Framework for Hardware-Accelerated Services Using Partially Reconfigurable SoCs - MACHIDON, O. M.; HINTEA, S.; SANDU, F. (Advances in Electrical and Computer Engineering)
The current trend towards ?Everything as a Service? fosters a new approach on reconfigurable hardware resources. This innovative, service-oriented approach has the potential of bringing a series of benefits for both reconfigurable and distributed computing fields by favoring a hardware-based acceleration of web services and increasing service performance. This paper proposes a framework for accelerating web services by offloading the compute-intensive tasks to reconfigurable System-on-Chip (SoC) devices, as integrated IP (Intellectual Property) cores. The framework provides a scalable, dynamic management of the tasks and hardware processing cores, based on dynamic partial reconfiguration of the SoC. We have enhanced security of the entire system by making use of the built-in detection features of the hardware device and also by implementing active counter-measures that protect the sensitive data.